2006
DOI: 10.1542/peds.2005-2140
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Flow-Mediated Vasodilation, Carotid Artery Intima-Media Thickening, and Elevated Endothelial Plasma Markers in Obese Children: The Impact of Cardiovascular Risk Factors

Abstract: The present study documented increased IMT, impaired endothelial function, and elevated plasma markers of endothelial activation and injury in obese children. Morbid obesity, arterial hypertension, subclinical inflammation, and low physical fitness formed a risk profile associated with the risk of early atherosclerosis in these children. Sonographic assessment of vascular status and the estimation of soluble endothelial plasma markers, combined with comprehensive risk factor screening, may form a rationale to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
4
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(174 citation statements)
references
References 48 publications
9
153
4
8
Order By: Relevance
“…D-dimers, fibrinogen, and vWFAg levels did not reach a significant correlation with vascular parameters. These results were in contrast with some previous literature studies, 11,[49][50][51][52] which reported the influence of such parameters on endothelial function and on vascular wall morphological structure. In fact, OrenesPiñero et al 53) pointed out the correlation between BMI and coagulation parameters, observing an increased prothrombotic status in adult subjects suffering from increased body weight.…”
Section: Discussioncontrasting
confidence: 99%
“…D-dimers, fibrinogen, and vWFAg levels did not reach a significant correlation with vascular parameters. These results were in contrast with some previous literature studies, 11,[49][50][51][52] which reported the influence of such parameters on endothelial function and on vascular wall morphological structure. In fact, OrenesPiñero et al 53) pointed out the correlation between BMI and coagulation parameters, observing an increased prothrombotic status in adult subjects suffering from increased body weight.…”
Section: Discussioncontrasting
confidence: 99%
“…In youths, plasma lipid profile is negatively associated with CVF in both overweight and non-overweight adolescents, 44 as well as total body fat, 10,11 abdominal adiposity, 8 features of the metabolic syndrome, 9,45 arterial compliance 46 and morphologic parameters reflecting early stage vascular changes, such as flow-mediated vasodilation and intima-media thickness. 47 However, others have failed to find associations between features of metabolic syndrome and CVF in overweight Latino youths aged 8-14 years with a positive family history of type 2 diabetes. 48 To our knowledge, there is no data examining the association of fibrinogen, C3 and C4 with CVF and fatness in prepubertal children.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid intima media thickness and distensibility, associated with age, anthropometry and BP are elevated in at-risk children with familial hypercholesterolaemia (115,116), overweight (117,118), HTN (119,120), and type 1 diabetes (121).…”
Section: Blood Vesselsmentioning
confidence: 99%